Detection and assessment of damage in underwater marine structures using image processing based techniques - O'Byrne, Michael (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2015)
The monitoring of underwater structures is often beset by limited access, exorbitant costs and inherent safety issues. This thesis focuses on developing and implementing automated image processing based Non-Destructive Testing (NDT) techniques to facilitate inspections. Adopting such techniques can vastly improve the condition of monitoring, reduce the operational complexities and partially offset the financial burden of regular inspections. To date, there has been very little work carried out on image based techniques for the purposes of detecting and quantifying the extent of structural damage particularly affecting the submerged part of marine structures.
Keywords: Civil, Structural and Environmental Engineering, Ph.D.; Ph.D. Trinity College Dublin